Deriving summary indices of health status from the Amyotrophic Lateral Sclerosis Assessment Questionnaires (ALSAQ-40 and ALSAQ-5). Issue 2 (1st February 2003) - Jenkinson, C; Norquist, J M; Fitzpatrick, R
Abstract : Objectives: To use statistical procedures, operationalising what is known as item response theory (IRT), to assess the unidimensionality of the 40 item Amyotrophic Lateral Sclerosis Assessment Questionnaire, and consequently to develop a single index figure from the measure. A secondary objective is to compare scores gained on the ALSAQ-40 with a five item short form (the ALSAQ-5). Methods: Postal survey of patients diagnosed with motor neurone disease (MND) on the MND Associations database. Copies of the ALSAQ-40 and, nested within it, the ALSAQ-5 were completed on two occasions. At time one, the survey contained the ALSAQ-40 and demographic questions. In addition, patients were asked to indicate if they were willing to take part in the follow up. Those who agreed to do so were sent another copy of the questionnaire after a period of three months. Respondents were also asked to indicate how much change they had experienced since baseline on each of the five domains of the questionnaire. Rasch analysis, a form of IRT methodology, was used to determine if the 40 items in the ALSAQ-40 tapped an underlying "latent trait", and were consequently measuring a unidimensional construct. The results from the ALSAQ-40 single index were then compared with those gained from the ALSAQ-5. Results: Analyses indicated that, at both baseline and follow up, all items on the ALSAQ-40 fitted the Rasch model. Consequently the 40 items were summed to create a single index. Results on this instrument were compared with those gained by summing the five items of the ALSAQ-5. Results on the instruments were found to be highly correlated. Conclusions: Evidence from the analyses suggests that 40 item ALSAQ does contain a unidimensional scale, and can, therefore be summed to create a single index. Furthermore the ALSAQ-5 closely replicates the results of the patient measure.